2018
DOI: 10.1186/s12885-018-4333-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-endometrioid and high-grade endometrioid endometrial cancers show DNA fragmentation factor 40 (DFF40) and B-cell lymphoma 2 protein (BCL2) underexpression, which predicts disease-free and overall survival, but not DNA fragmentation factor 45 (DFF45) underexpression

Abstract: BackgroundThe expression of DNA fragmentation factor 45 (DFF45) and B-cell lymphoma 2 (BCL2) in glands of the normal human endometrium is related to phases of the menstrual cycle and decreases after menopause, whereas the expression of DNA fragmentation factor 40 (DFF40) is stable. Moreover, DF45, BCL2 and DFF40 underexpression has been reported in numerous malignancies, including uterine leiomyosarcomas. In this study, we aimed to investigate DFF45, BCL2 and DFF40 expression in endometrioid and non-endometrio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…Similar alterations in expression patterns of the individual proteins have previously been demonstrated and extensively linked to LNM by us and others. 18 , 55 57 These findings support that LIMMA correctly identifies proteins associated with nodal metastasis and indicate that multiple proteins are involved; our model only selects the most contributing proteins. However, functional studies are needed to build up a picture of protein networks that drives metastasis.…”
Section: Discussionsupporting
confidence: 71%
“…Similar alterations in expression patterns of the individual proteins have previously been demonstrated and extensively linked to LNM by us and others. 18 , 55 57 These findings support that LIMMA correctly identifies proteins associated with nodal metastasis and indicate that multiple proteins are involved; our model only selects the most contributing proteins. However, functional studies are needed to build up a picture of protein networks that drives metastasis.…”
Section: Discussionsupporting
confidence: 71%
“…Type II endometrial carcinomas are usually characterized by p53 and PIK3CA overexpression, while type I tumors are characterized by PTEN mutations (15) . Also, type II endometrial carcinomas compared to type I showed significant DFF40 and BCL2 underexpression as reported by Banas et al (16) . Minimally invasive surgery has been widely accepted to be used as the preferred approach in type I endometrial cancers and in selected cases of type II endometrial cancer (3,7,17,18) .…”
supporting
confidence: 78%
“…Finally, caspase-3/7 activity was assessed by flow cytometer with the Caspase-3/7 Green detection reagent (Thermo Fisher Scientific, Cat#R37111) according to the manufacturer's instructions with some modifications. Briefly, 1x10 6 Jurkat cells were treated or not with STS [1 µM] for up to 2, 4 and 6 h in RPMI medium supplemented with 0.1% FBS. Cells were then washed twice with PBS 1X and suspended in PBS 1X containing the caspase-3/7 probe (3 drops in 4 ml).…”
Section: Apoptosis Assessmentmentioning
confidence: 99%
“…Extracellular acidification rates (ECAR) and oxygen consumption rates (OCR) were assessed using the Seahorse XF Cell Mito Stress Test Kit (Agilent Cat#103015), according to the manufacturer's instructions with some modifications. Briefly, Jurkat cells were seeded in Seahose XFe96 cell culture microplates at a density of 0.2x10 6 Briefly, Jurkat DFF40 WT and DFF40 KO cells were washed once with PBS 1X and suspended in complete RPMI medium and fixed with 4% (v/v) paraformaldehyde for 15 min at room temperature. Samples were then vortexed 5 min at 400xg and pellets were suspended in PBS 1X.…”
Section: Seahorse Assaymentioning
confidence: 99%
See 1 more Smart Citation